Pengembangan Media Interaktif Wordwall pada Pembelajaran Pendidikan Pancasila Elemen NKRI Sekolah Dasar - Reinita Reinita; Ainila Pradi Sespen (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
Learning is the motivation that teachers give to students to acquire knowledge. This research aims to develop Wordwall interactive media for Pancasila Education on elements of the Unitary State of the Republic of Indonesia (NKRI) using the Problem Based Learning (PBL) model in grade IV of Elementary School Cluster 1, West Padang District. This development aims to make the media valid, practical, and effective. The type of research used is Research and Development (R&D) with a 4D model. The research was carried out in elementary schools by collecting data through questionnaires from material experts, languages, media, and teacher and student responses. The trial subjects consisted of 28 grade IV students at SDN 24 Ujung Gurun and 28 students at SDN Pertryan Padang. The results of the study show that Wordwall interactive media received a value of 95% material validity, 95% language, and 87.5% media, all in the valid category. The practicality test of the teacher's response resulted in 89.5% and the student's response 91.7%, both in the very practical category. The effectiveness test showed a result of 91%, which is in the very high category. Thus, the Wordwall interactive media is declared valid, practical, and effective for learning Pancasila Education in grade IV of Elementary School.